Islamic Corporate Social Responsibility: Praktik Bisnis Berbasis Nilai Islam Pada Paragon Corp - Rizky Aditya Ramadhan; Nayla Ramadhani; Andika Febriansyah; Abdul Fadhil (JURNAL EKOMAKS Jurnal Ilmu Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the implementation of Islamic Corporate Social Responsibility (CSR) in PT. Paragon Technology and Innovation, is one of Indonesia's leading cosmetic companies. The study examines how the company applies Islamic values in its CSR practices and identifies the correlation between CSR implementation at PT. Paragon Technology and Innovation with Islamic values, and explores the opportunities for expanding positive impacts. Using a qualitative case study approach and maudhu ‘iy analysis, the research found that Islamic CSR implementation supports business sustainability and contributes significantly to holistic community welfare.